De la o educaţie muzicală permanentă spre o educaţie permanentă prin muzică [Articol] - Cosumov, Marina (USARB, 2016)
Education is a sustainable human development strategic resource in postmodern society, being historically, culturally, socially, economically placed in time and space. The educational reform, based on curricular approach, involves radical changes in musical and artistic education, and this is "a precondition for the formation of an intelligent personality, with high moral and spiritual aspirations" (Coroi 2010: 4). The promotion of arts products will foster musical artistic scope concern and will ensure continuity in connection with music.
Keywords: educaţie muzicală; educaţie artistică; valori muzicale; cunoştinţe artistice; permanent musical and artistic education; musical values